Engineering Drawing Training for High School/Vocational School Teachers in Jakarta Using AUTOCAD MECHANICAL - Herry Susanto; Husen Asbanu; Yefri Chan; Yendi Esye; Darsono (JEPTIRA, 2024)
The primary objective of this community service initiative is to provide training to high school and vocational school instructors in Jakarta on the use of AutoCAD Mechanical for engineering drawing. AutoCAD Mechanical offers sophisticated automation features and tools to enhance the accuracy and productivity of technical drawings. The training was conducted online, which enabled a wide range of participants to participate. The methodology comprised a pre-test to evaluate initial knowledge, interactive sessions to convey material, and a post-test to evaluate learning outcomes. The training was attended by a total of 33 participants. The findings suggest that the majority of participants developed a more comprehensive comprehension of the ethical implications and precision of AI-based tools. The discussion emphasizes the efficacy of online training in improving the understanding of AutoCAD Mechanical among instructors. For future enhancements and future reference, documentation was maintained, which encompassed participant engagement and training activities. This activity enhances the proficiency of educators in the utilization of digital tools for the purpose of mechanical engineering education.